EU policies and global food security - Jean-Christophe Bureau; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
This paper reviews evidence on the impact of EU policies on global food security, focusing on four EU policy areas: agricultural policy, bioenergy policy, trade policy, and development (food aid) policy. Old concerns related to the detrimental impact of EU farm subsidies, food aid and tariffs on poor countries' food security. New concerns relate to impacts of EU food standards and bioenergy policies. The EU policies which created the largest distortions on global markets (in the area of trade, agriculture, food aid, and bioenergy) have been substantially reformed over the past decades. Recent global food price fluctuations have also re-emphasized that the impact of EU policies on the poor's food security differ depending on whether these are consumers or producers, or whether countries are exporters or importers. Overall, our review explains that in many areas the impact of EU policies on global food security is less obvious and more complex than often argued.
Keywords: 330